A Meta-Analysis of Survival Outcomes Following Reoperation in Recurrent Glioblastoma: Time to Consider the Timing of Reoperation - Zhao, Yu-Hang; Wang, Ze-Fen; Pan, Zhi-Yong; Péus, Dominik; Delgado-Fernandez, Juan; Pallud, Johan; Li, Zhi-Qiang (Frontiers in Neurology, 2019)
Background: Glioblastoma multiforme (GBM) inevitably recurs, but no standard regimen has been established for recurrent patients. Reoperation at recurrence alleviates mass effects, and the survival benefit has been reported in many studies. However, in most studies, the effect of reoperation timing on survival benefit was ignored. The aim of this meta-analysis was to investigate whether reoperation provided similar survival benefits in recurrent GBM patients when it was analyzed as a fixed or time-dependent covariate. Methods: A systematic literature search of PubMed, EMBASE, and Cochrane databases was performed to identify original articles that evaluated the associations between reoperation and prognosis in recurrent GBM patients. Results: Twenty-one articles involving 8630 patients were included. When reoperation was considered as a fixed covariate, it was associated with better overall survival (OS) and post-progression survival (PPS) (OS: HR=0.66, 95% CI 0.61-0.71, p<0.001, I2=0%; PPS: HR=0.70, 95% CI 0.57-0.88, p<0.01, I2=70.2%). However, such a survival benefit was not observed when reoperation was considered as a time-dependent covariate (OS: HR=2.19, 95% CI 1.47-3.27, p<0.001; PPS: HR=0.95, 95% CI 0.82-1.10, p=0.51, I2=0%). The estimate bias caused by ignoring the time-dependent nature of reoperation was further demonstrated by the re-analysis of survival data in three included studies. Conclusions: The timing of reoperation may have an impact on the survival outcome in recurrent GBM patients, and survival benefits of reoperation in recurrent GBM may be overestimated when analyzed as fixed covariates. Proper analysis methodology should be used in future work to confirm the clinical benefits of reoperation.